2019
DOI: 10.1590/0034-7167-2018-0264
|View full text |Cite
|
Sign up to set email alerts
|

Images of alcohol in the adolescents’ life of one quilombola community

Abstract: Objective: To analyze the images of alcohol in the rite of passage of adolescents of a quilombola community. Method: Qualitative and participatory study was developed by Creative and Sensitive Method, and guided by generated questions: “In my house, alcohol is...”; “Near my house, I see alcohol in...” Ten adolescents who live in a quilombola community in the north of the state of Espírito Santo, Brazil, participated in the group dynamics. The material was submitted to a thematic analysis. Results: Images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Ethnographic study 24 developed in the same Quilombola community of this research, reveals that there is a tendency of the younger members to follow the professional model of parents and/or their ancestors, where they are stimulated by the family and the Agricultural Family Schools, which in addition to teaching disciplines of the curricular component, stimulate learning and professional training for the young person in the field, qualifying them both to continue their studies, as well as to dedicate themselves to family farming or other properties. Those who wish to acquire another type of training, seek the headquarters of the municipality that is 44 kilometers from the community, a practice not common due to the related high costs, mainly, to transportation and food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnographic study 24 developed in the same Quilombola community of this research, reveals that there is a tendency of the younger members to follow the professional model of parents and/or their ancestors, where they are stimulated by the family and the Agricultural Family Schools, which in addition to teaching disciplines of the curricular component, stimulate learning and professional training for the young person in the field, qualifying them both to continue their studies, as well as to dedicate themselves to family farming or other properties. Those who wish to acquire another type of training, seek the headquarters of the municipality that is 44 kilometers from the community, a practice not common due to the related high costs, mainly, to transportation and food.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption in adolescence was also evidenced in the discourses, where the girl must stop drinking so as not to cause harm to her child, who considers herself a responsible attitude for adolescents. A Study 24 showed that alcohol in the Quilombola community is culturally and socially accepted. Alcohol consumption is more evident among men, represented by the image of their father, uncle and grandfather, than among women.…”
Section: /15mentioning
confidence: 99%
“…Professionals need to be immersed in the reality of the population, in order to consider the values and experiences of the community's way of life, to reflect on their performance and, more intensely, they need to do it in a critical and responsible manner. This will impact actions that can free the community from the determinant condition of existing social vulnerability (11,(28)(29) .…”
Section: Discussionmentioning
confidence: 99%
“…Nursing care is produced from technical and relational knowledge that can lead to responses to individuals and communities, guided by SUS principles, provides the reduction of vulnerabilities (1) . The practice of care based on cultural and political competences has a creative character, with respect for the knowledge, values and experiences of others, enhancing the emancipatory actions and freedom of both scientific and empirical knowledge (29) .…”
Section: Discussionmentioning
confidence: 99%
“…(McNiff, 2007) Particularmente relevante para a abordagem de temas sensíveis, ou seja, aqueles que apresentam elevada carga de estigma e preconceito, porque sua construção social está associada a sentimentos negativos que provocam desconfortos e constrangimentos. (Partelli & Cabral, 2019;Caldas, Dias, Sousa, & Teixeira, 2019).…”
Section: Metodologiaunclassified